2012
DOI: 10.1100/2012/973058
|View full text |Cite
|
Sign up to set email alerts
|

Durum Wheat in Conventional and Organic Farming: Yield Amount and Pasta Quality in Southern Italy

Abstract: Five durum wheat cultivars were grown in a Mediterranean area (Southern Italy) under conventional and organic farming with the aim to evaluate agronomic, technological, sensory, and sanitary quality of grains and pasta. The cultivar Matt produced the best pasta quality under conventional cropping system, while the quality parameters evaluated were unsatisfactory under organic farming. The cultivar Saragolla showed the best yield amount and pasta quality in all the experimental conditions, thus proving to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
5
26
0
Order By: Relevance
“…IWF was obtained from immature seeds harvested during milk ripeness (1 to 2 weeks after anthesis) of durum wheat (Triticum durum Desf.) variety Grace cultivated on the Torre Lama experimental farm (Campania, Italy; 40°37=N, 14°58=E, 30 m above sea level), located in an area suitable for the production of good-quality wheat and pasta (20). Wheat flour type 0 America was used for the preparation of flour mixtures employed in dough and sourdough making.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IWF was obtained from immature seeds harvested during milk ripeness (1 to 2 weeks after anthesis) of durum wheat (Triticum durum Desf.) variety Grace cultivated on the Torre Lama experimental farm (Campania, Italy; 40°37=N, 14°58=E, 30 m above sea level), located in an area suitable for the production of good-quality wheat and pasta (20). Wheat flour type 0 America was used for the preparation of flour mixtures employed in dough and sourdough making.…”
Section: Methodsmentioning
confidence: 99%
“…As reported by Escalada and Mos (12), D'Egidio et al (18), and Mujoo and Ng (19), the high FOS content in immature wheat flour (IWF) suggested its use as a prebiotic ingredient for the development of new functional foods. It could represent added value and an alternative to the traditional uses of durum wheat (20). From an agronomic point of view, the soil released after early harvesting may be allocated to new production.…”
mentioning
confidence: 99%
“…Among the several aspects of organic wheat production, N management is crucial (Bilsborrow et al, 2013), particularly for autumn-sown wheat in the Mediterranean area, as low organic matter content in the soil, low temperatures, and high autumnspring rainfall can cause very low levels of available mineral N in the soil during most of the crop cycle (Fagnano et al, 2012). In conventional agriculture, the use of split application of mineral N fertilizers has been shown to increase fertilization effi ciency and the harvest index of wheat (Blandino et al, 2015;FuertesMendizábal et al, 2010).…”
mentioning
confidence: 99%
“…However, differences between the new and old varieties were very minor or absent when they were grown in the presence of weed competition and under low N availability, conditions typical in organic farming. Fagnano et al (2012) observed no significant interaction between cropping systems (conventional and organic) and spring durum genotypes regarding yield and yield components, but average yields in the organic system were 21% lower than in the conventional one. Modern durum varieties seem unable to express their yield potential when grown under organic or low input farming conditions (Dinelli et al 2013), so there is a need to develop, or at least identify durum genotypes that can provide adequate performance without high nitrogen inputs by selecting specific traits, such as kernel weight, spike length and kernels/spike (Dinelli et al 2014).…”
Section: Introductionmentioning
confidence: 70%